Predicatori e moltitudini: dare un volto alla folla (secolo XIII) - Pietro Delcorno (Artes)
Starting from the famous scenes of Antony of Padua’s sermon to the fishes and Francis of Assisi’s preaching to the birds, this article shows how the Friar minors’ preaching formed a discursive space that gave voice and representation to new segments of thirteenth-century urban society. From Francis’ experimental initiatives to Anthony of Padua’s and Berthold of Regensburg’s well-planned preaching campaigns, the friars were able to speak to a society undergoing profound transformation and marked by tensions and fears. The crowds gathering to hear the preachers were moved by the perception that what was being stated in an accessible language was actually relevant to their lives. Somehow, as part of this communicative process, the preacher addressed a large crowd and yet each person in the audience – at least at some points – had the impression that he or she was the preacher’s actual addressee, as in a personal conversation. That is to say, they had the feeling that they were real interlocutors, not a shapeless mob.